The development of RAMSIS in past and future as an example for the cooperation between industry and university. (15th December 2006) - Bubb, Heiner; Engstler, Florian; Fritzsche, Florian; Mergl, Christian; Sabbah, Olaf; Schaefer, Peter; Zacher, Iris
The digital human model RAMSIS was developed enforced by the German automotive industry by the cooperation of the commercial enterprise Tecmath and the Institute of Ergonomics of the Technische Universitat Munchen. During the first development phase from 1986–1993 the anthropometric model and a posture prediction model with integrated discomfort evaluation based on joint angles was created. In the second and the actual phase, a strength model is added, which allows evaluating discomfort also by the exploitation of maximum strengths. Further the contact between the seat and the digital model can be calculated and evaluated on the basis of extensive experiments. Actually a model of motion prediction is developed that allows simulating motions depending on external conditions defined by CAD data. Further research is done to predict the dynamic discomfort during this motion.